Derivaçao de uma Equação Diferencial Parcial Não-Linear na Propagação de Frentes de Reação em Química - CARDOSO FILHO, João Lopes (2008)
In this dissertação we deducted a nonlinear evolution equations which model vertical propagation of chemical reaction fronts. We establish which the initial value problem ∂tu - ∂²x u - ½(∂xu)² - µ(1-∂²x) - ½u = 0, x Є [-π, π], t > 0 u(.,0) = ø, 2 π - periódica it is a the Cauchy problem locally well-posed.